Altered plasma glutathione levels in bipolar disorder indicates higher oxidative stress; a possible risk factor for illness onset despite normal brain-derived neurotrophic factor (BDNF) levels. Issue 11 (27th January 2014) - Rosa, A. R.; Singh, N.; Whitaker, E.; de Brito, M.; Lewis, A. M.; Vieta, E.; Churchill, G. C.; Geddes, J. R.; Goodwin, G. M.
Abstract : Background: Oxidative stress and neurotrophic factors have been implicated in the pathophysiology of bipolar disorder. Our objective was to determine whether plasma glutathione or brain-derived neurotrophic factor (BDNF) levels were abnormal in bipolar disorder and therefore useful as possible biomarkers. Method: Blood samples were collected from subsyndromal, medicated bipolar I patients ( n  = 50), recruited from OXTEXT, University of Oxford, and from 50 matched healthy controls. Total and oxidized glutathione levels were measured using an enzymatic recycling method and used to calculate reduced, percentage oxidized, ratio of reduced:oxidized and redox state. BDNF was measured using an enzyme-linked immunoassay. Self-monitored mood scores for the bipolar group were available (Quick Inventory of Depressive Symptomatology and the Altman Self-Rating Mania Scale) over an 8-week period. Results: Compared with controls, bipolar patients had significantly lower levels of total glutathione and it was more oxidized. BDNF levels were not different. Age of illness onset but not current mood state correlated with total glutathione levels and its oxidation status, so that lower levels of total and reduced glutathione were associated with later onset of disease, not length of illness. Conclusions: Plasma glutathione levels and redox state detect oxidative stress even in subsyndromal patients with normal BDNF. It may relate to the onset and development of bipolar disorder. Plasma glutathione appears to be a suitable biomarker for detecting underlying oxidative stress and for evaluating the efficacy of antioxidant intervention studies.